(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Robert-Andrei Stoica explores the connection between Early Christian mural art in Dobruja and Mihai Eminescu's fantastic prose. The study analyzes how symbols found in ancient tombs—such as the orange, the poppy, and the rose—reappear in Eminescu’s literature as psychopomp elements. By drawing parallels between archeological findings in Constanța and the poet's descriptions, the author demonstrates that Eminescu uses mural art to symbolize the soul's journey into the afterlife and transcendent salvation. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.